PUNARNAVASHTAKA KSHEERABASTI IN THE MANAGEMENT OF EDEMA IN PREGNANCY: A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2017)
Edema is a common physiological symptom in the late pregnancy. The incidence of dependent edema in normal healthy pregnant women is reported to be 50-80% in third trimester. It is caused mainly due to sub-cutaneous fluid retention and by the pressure of the expanding uterus on the vessels supplying the lower extremities. In Ayurveda, Shotha (edema) in pregnancy is described in the context of Garbhini Vyadhi (disorders of pregnancy). Punarnavashtaka Kwatha having the Shothahara property is therefore been taken up in this case and is administered in Ksheerpaka form and given as Basti (enema). In this case study a 20 year old pregnant lady with 36 weeks 4 days of amenorrhoea, complaining of edema in the extremities and face along with scanty and burning micturation associated with pain abdomen was treated with Punarnavashtaka Kwatha Ksheera Basti, administered for 10 days once in the morning in the dose of 450 ml per day. Patient got complete relief from the edema, pain and urinary complaints within the course of treatment period. Pregnancy related physiological edema, anemia and urinary discomforts can be treated by Punarnavashtaka Kwatha Ksheera Basti alone. It prevents further complications of edema, without any undue side effects, with economical and easy administration.